User satisfaction as a quality indicator in the municipal sports service. Perception, analysis and evolution - Armada, E.; Martínez -Gallego, F.; Segarra, E.; Díaz, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
A longitudinal study will be conducted which can be useful for the benchmarking of future public sports managers. The objectives of this study will be determining the degree of present user satisfaction with communal sports services offered by the city council of Cartagena, analyzing the development of user satisfaction over time, between 1991 and 2015, in order to update quality levels offered by those services and providing a practical example of management that is quality oriented. The global analysis of the dimensions of the survey shows that all resources of the communal sports services determine the quality although some are more important that others concerning the satisfaction of the citizens, the most important part of the organization at both times are the people who provide the service. The data will ensure that decisions will be made to enhance those aspects that were rated the worst by the users and that systems will be applied to secure quality, satisfaction and citizen loyalty to the communal sports services.